Nieznana korespondencja Władysława Reymonta - Bourkane, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
This study is an edition of two unpublished letters by Władysław Reymont from January and May 1895. Both epistolary testimonies, related to the writer’s journey to Italy, significantly expand our knowledge of the relatively early period in his literary biography.